Epigenetic regulation – contribution to herbicide resistance in weeds?. Issue 2 (1st November 2017) - Markus, Catarine; Pecinka, Ales; Karan, Ratna; Barney, Jacob N; Merotto, Aldo
Abstract: Continuous use of herbicides has resulted in the evolution of resistance to all major herbicide modes of action worldwide. Besides the well‐documented cases of newly acquired resistance through genetic changes, epigenetic regulation may also contribute to herbicide resistance in weeds. Epigenetics involves processes that modify the expression of specific genetic elements without changes in the DNA sequence, and play an important role in re‐programming gene expression. Epigenetic modifications can be induced spontaneously, genetically or environmentally. Stress‐induced epigenetic changes are normally reverted soon after stress exposure, although in specific cases they can also be carried over multiple generations, thereby having a selective benefit. Here, we provide an overview of the basis of epigenetic regulation in plants and discuss the possible effect of epigenetic changes on herbicide resistance. The understanding of these epigenetic changes would add a new perspective to our knowledge of environmental and management stresses and their effects on the evolution of herbicide resistance in weeds. © 2017 Society of Chemical Industry Abstract : Epigenetic regulation is associated with evolution of drug resistance in humans. Here, we provide an overview about the possible effects of epigenetic changes on herbicide resistance, mainly to non‐target‐site mechanisms.